GHRITA MURCHANA WITH RESPECT TO COMPARATIVE PHYSICO-CHEMICAL ANALYSIS OF PLAIN GHRITA AND MURCHIT GHRITA - Choudhary, Neelam; Narode, Sagar (International Journal of Ayurveda and Pharma Research, 2015)
Background: Sneha Kalapana is a unique contribution to Ayurvedic science. Ghrita Murchana is a special pharmaceutical procedure before subjecting the drugs to Snehapaka and is used for Amadoshaharatwa, removal of odor, imparting color and increasing potency of the drug.Methods: Murchana of Ghrita was done as mentioned in Bhaishajya Ratnavali. Physico-chemical analysis of Plain and Murchit Ghrita were done and comparison of various parameters on quality assessment was done.Result: Physicochemical parameters were applied for assessing the prepared formulation. The refractive index was 1.4560. The specific gravity of the sample was 0.9138, which was closer to plain Ghrita, for which it was 0.9, showing that the sample was not too dense. The acid value was 0.556, indicating the amount of free fatty acid present in the Ghrita. The acid value decreased considerably from 0.868 to 0.556 which shows decrease in rancidity.Conclusion: We conclude that the Murchana of Ghrita showed that with Murchana, Ghrita becomes a very effective medium for drugs. It helps in decreasing rancidity, removing odor and imparting it a greenish-yellow color.